Assessing the association between supplemented puppyhood dietary fat sources and owner-reported epilepsy in adulthood, among Finnish companion dogs - Hemida, Manal; Rosendahl, Sarah; Jokinen, Tarja S.; Moore, Robin; Vuori, Kristiina A.; Anturaniemi, Johanna; Hielm-Björkman, Anna (Frontiers in Veterinary Science, 2023)
A nested case-control study was compiled from the validated DogRisk food frequency questionnaire (DogRisk FFQ) to analyze whether feeding dietary fat sources during puppyhood was associated with canine epilepsy in adulthood. The DogRisk FFQ collected feeding, disease, and background data about the dog. The study sample consisted of 108 owner-reported epileptic cases and 397 non-epileptic controls. Each case was matched with up to four controls for the key confounding factors of sex, breed, and age. We analyzed associations between feeding as a puppy and owner-reported epilepsy as an adult dog, using Cox regression. We tested 55 different food variables. Among all, we found that feeding fish fat from dietary sources at least once a week during puppyhood was inversely associated with the epilepsy in later life in unadjusted analysis (OR 0.46 (95% CI 0.25-0.83), p =0.01), while when adjusted for keeping conditions and dog characteristics the association was (OR 0.45 (95% CI 0.23-0.88), p =0.02). Adjusted for keeping conditions, dog characteristics and other feeding factors, the association was of similar magnitude but did not reach significance (OR 0.56 (95% CI 0.27-1.15), p =0.12). The study indicates possible protective associations of feeding the dog with dietary sources of fish fat against epilepsy, although the result could be confounded by other feeding factors. Findings are compatible with what is known about the role of omega-3 fatty acids as well as the ketogenic diet, a diet including a high dietary fat content, as supportive treatments of epilepsy. As our findings are based on observations, we suggest the possibility of causality but do not prove it. Dietary intervention studies should now be conducted to confirm our findings.